IAIN Bone Academics on Rahn Collateral Utilization:Hadith Authentication and Legal Analysis - bin Junaid, Junaid; Muh. Nasruddin A; Hariri Junaid, Ahmad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
This study explores the use of pawned goods (rahn) in the perspective of hadith and its relevance in contemporary Islamic financial practices. This study aims to analyze the textual authority of rahn hadith, examine its legal implications in both classical and contemporary Islamic jurisprudence, and explore how Muslim scholars interpret its application in the Indonesian context. This research is a qualitative research with a normative-empirical design. The subjects of the study are six IAIN Bone academics who have expertise in hadith, jurisprudence, muamalat and sharia economics. Research data was collected through literature studies, semi-structured interviews and documentation. The data analysis technique is carried out through the analysis of hadith takhrij, comparative fiqh studies as well as reduction, categorization and thematic conclusions. The results of the study show that the hadith about the ability to use pawned animals has a valid status, but its application in the context of modern economics requires contextual reading. Academics tend to emphasize the principles of sharia maqashid, distributive justice and debtor protection in rahn practice. Therefore, the use of pawned goods must be limited to real cost compensation and must not be an instrument of economic exploitation in the Islamic financial system.